Rod-cone signal interference in the retina shapes perception in primates - Songco-Aguas, Adree; Grimes, William N.; Rieke, Fred (Frontiers in Ophthalmology, 2023)
Linking the activity of neurons, circuits and synapses to human behavior is a fundamental goal of neuroscience. Meeting this goal is challenging, in part because behavior, particularly perception, often masks the complexity of the underlying neural circuits, and in part because of the significant behavioral differences between primates and animals like mice and flies in which genetic manipulations are relatively common. Here we relate circuit-level processing of rod and cone signals in the non-human primate retina to a known break in the normal seamlessness of human vision – a surprising inability to see high contrast flickering lights under specific conditions. We use electrophysiological recordings and perceptual experiments to identify key mechanisms that shape the retinal integration of rod- and cone-generated retinal signals. We then incorporate these mechanistic insights into a predictimodel that accurately captures the cancellation of rod- and cone-mediated responses and can explain the perceptual insensitivity to flicker.